2017
DOI: 10.1002/maco.201709794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of machining on the stress corrosion cracking behavior in boiling magnesium chloride solution of austenitic stainless steel

Abstract: The stress corrosion cracking (SCC) behaviors of Z3CN20.09M, 304L, and 316L austenitic stainless steels (SSs) after milling operation in boiling magnesium chloride solution were investigated by scanning electron microscopy (SEM), X‐ray diffraction, and 3D profilometer. The experimental results indicated that the roughness and residual stress increased with increasing feed rate of all specimens. The depth of deformation layer after milling operation reached about 150 µm shown as persistent slip bands (PSBs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The strength of ferrite was higher than austenite when the composition and manufacture technology were similar, so the crack propagation was often postponed by ferrite . In our previous study, the postponed cracks were observed at the milled surface, and the similar phenomenon was also observed at the cross section of deformation layer.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The strength of ferrite was higher than austenite when the composition and manufacture technology were similar, so the crack propagation was often postponed by ferrite . In our previous study, the postponed cracks were observed at the milled surface, and the similar phenomenon was also observed at the cross section of deformation layer.…”
Section: Resultssupporting
confidence: 76%
“…In boiling magnesium chloride solution condition, the cracking often occurred intracrystalline, while the IG cracking was aroused after milling operations, as mentioned previously . This could be attributed to the damage effect on the grain boundary was revealed with increasing the feed rate during milling operation, as indicated in our previous study.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…There are several parameters to establish the surface roughness value. The surface roughness average is the most widely used in the industry thanks to the ease with which it can be assessed (generally after processing) and the closeness with which it represents the surface texture of the mechanized part [32,33].…”
Section: Concepts and Related Workmentioning
confidence: 99%
“…SCC is the main corrosion failure mode for 310S stainless steels and it is characterized by the slow nucleation and propagation of cracks on the material under the synergic interaction of mechanical tension and a specific corrosive environment [3,4]. In general, the nucleation of stress corrosion cracks occurs at stress levels below the yield stress of the materialand SCC full failure could occur at stresses below the material's ultimate tensile strength [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%